Pharmacological and mechanistic aspects of quercetin in osteoporosis - Deng, Ting-Ting; Ding, Wen-Yu; Lu, Xi-Xue; Zhang, Qing-Hao; Du, Jin-Xin; Wang, Li-Juan; Yang, Mei-Na; Yin, Ying; Liu, Fan-Jie (Frontiers in Pharmacology, 2024)
Osteoporosis (OP) is a bone disease associated with increasing age. Currently, the most common medications used to treat OP are anabolic agents, anti-resorptive agents, and medications with other mechanisms of action. However, many of these medications have unfavorable adverse effects or are not intended for long-term use, potentially exerting a severe negative impact on a patient's life and career and placing a heavy burden on families and society. There is an urgent need to find new drugs that can replace these and have fewer adverse effects. Quercetin (Que) is a common flavonol in nature. Numerous studies have examined the therapeutic applications of Que.However, a comprehensive review of the anti-osteoporotic effects of Que has not yet been conducted. This review aimed to describe the recent studies on the anti-osteoporotic effects of Que, including its biological, pharmacological, pharmacokinetic, and toxicological properties.The outcomes demonstrated that Que could enhance OP by increasing osteoblast differentiation and activity and reducing osteoclast differentiation and activity via the pathways of Wnt/β-catenin, BMP/SMAD/RUNX2, OPG/RANKL/RANK, ERK/JNK, oxidative stress, apoptosis, and transcription factors. Thus, Que is a promising novel drug for the treatment of OP.Osteoporosis (OP) is the most prevalent type of systemic bone disease and is characterized by decreased bone mass and damage to the microstructure of the bone tissue, leading to increased bone fragility (Kanis et al., 2019). Patients with OP are more prone to fractures. Over 200 million people worldwide have OP (Palacios et al., 2022). The lifetime risk of developing the disease in Caucasian women aged >50 years is 50%, and OP-induced fractures can result in substantial medical expenses (up to $25.3 billion by 2025) and impaired physical function (Armas et al., 2012).Nearly all clinical medicine preparations are derived from natural compounds found in plants, animals, insects, marine organisms, and microbes (Harvey et al., 2015). Among them, flavonoids